Risk Factors, Causes, and Strategies for Reducing Medication Errors: A Narrative Review - Nadem, Suha; Makarim M. Ali Hassan,; Amena Lafeta Muttlaq Al-Shareefi, (University of Thi-Qar Journal of Science, 2024)
Abstract— Medication errors, which refer to any deviation from the prescribed medication regimen, can have seriously affected patient safety and treatment outcomes. It underscores the need for healthcare professionals to follow medication orders precisely and to be vigilant in preventing errors throughout the medication use. This process involves different stakeholders, including specialists, therapists, apothecaries, patients, and their relatives. Medication errors tend to be more prevalent in hospital settings due to various factors related to the complexity of patient care, the fast-paced environment, and the involvement of multiple healthcare professionals in the medication process. The current review was conducted for reporting medication errors, risk factors, causes, and strategies for reducing medication errors in previous articles from 2015 to 2023. The brief review showed that multiple studies have reported a high incidence of medication errors following hospital discharge. These errors can include prescribing errors, incorrect dosing, medicine interactions, and omissions or duplications of medication. Medication errors following hospital discharge can lead to adverse drug events, which can result in patient harm, hospital readmissions, and increased healthcare costs. Also; some studies have evaluated the effectiveness of transitional care interventions and strategies in reducing medication errors and adverse drug events (ADEs). These interventions can include medication reconciliation processes, post-discharge follow-up, patient education programs and electronic medication management system. By addressing these interventions, future studies and interventions can contribute to improving medication safety following hospital discharge and advancing the global safety agenda.